Data from: Discovery of a multi-species shark aggregation and parturition area in the Ba Estuary, Fiji Islands - Vierus, Tom; Gehrig, Stefan; Brunnschweiler, Juerg M.; Glaus, Kerstin; Zimmer, Martin; Marie, Amandine D.; Rico, Ciro (Dryad, 2019)
Population declines in shark species have been reported on local and
global scales, with overfishing, habitat destruction and climate change
posing severe threats. The lack of species-specific baseline data on
ecology and distribution of many sharks, however, makes conservation
measures challenging. Here we present a fisheries-independent shark survey
from the Fiji Islands, where scientific knowledge on locally occurring
elasmobranchs is largely still lacking despite the location’s role as a
shark hotspot in the Pacific. Juvenile shark abundance in the fishing
grounds of the Ba Estuary (north-western Viti Levu) was assessed with a
gillnet- and longline-based survey from December 2015 to April 2016. A
total of 103 juvenile sharks identified as blacktip Carcharhinus limbatus
(n = 57), scalloped hammerhead Sphyrna lewini (n = 35), and great
hammerhead Sphyrna mokarran (n = 11) sharks were captured, tagged, and
released. The condition of umbilical scars (68 % open or semi-healed),
mean sizes of individuals (± SD) (C. limbatus: 66.5 ± 3.8 cm, S. lewini:
51.8 ± 4.8 cm, S. mokarran 77.4 ± 2.8 cm), and the presence of these
species over recent years (based on fishermen interviews), suggest that
the Ba Estuary area is a critical habitat for multiple species that are
classified as “Near Threatened” or “Endangered”. Specifically, the area
likely acts as a parturition ground over the studied period, and
potentially as a subsequent nursery area. We identified subareas of high
abundance and found that temperature, salinity and depth acted as
small-scale environmental drivers of shark abundance. The data suggests a
tendency for species-specific spatial use, both horizontally (i.e. between
sampling areas) and vertically (i.e. across the water column). These
results enhance the understanding of shark ecology in Fiji and provide a
scientific basis for the implementation of local conservation strategies
that contribute to the protection of these threatened species.
Full data for Vierus et al. 2018The archive consists of a readme.txt and
two Excel tables, one of which contains all variables associated with gear
deployments in the fishery-independent survey (e.g., environmental
parameters, captures) and the other one contains all variables related to
individual sharks that were caught in the survey (e.g., total length,
sex).Vierus et al. 2018 - data.zip
Keywords: elasmobranchs; Sphyrna mokarran; blacktip sharks; shark bycatch; hammerhead sharks; Sphyrna lewini; Neonates; Carcharhinus limbatus; Young-of-the-year sharks